The plebeian republic : the Huanta rebellion and the making of the Peruvian state, 1820-1850 - Méndez G., Cecilia (e-Duke books scholarly collection., 2005)
Examines the politics of a 19th c. peasant revolt in Peru, looking at the organization and practice of government by the rebels to examine what a largely illiterate population understood by terms such as "nation" and showing the rebellion's sign.